A cost-effectiveness analysis of South Africa’s seasonal influenza vaccination programme - Edoka, Ijeoma (Vaccine, 2020)
BACKGROUND: Seasonal influenza imposes a significant health and economic burden in South Africa, particularly in populations vulnerable to severe consequences of influenza. This study assesses the cost-effectiveness of South Africa’s seasonal influenza vaccination strategy, which involves vaccinating vulnerable populations with trivalent inactivated influenza vaccine (TIV) during routine facility visits. Vulnerable populations included in our analysis are persons aged ≥ 65 years; pregnant women; persons living with HIV/AIDS (PLWHA), persons of any age with underlying medical conditions (UMC) and children aged 6–59 months. METHOD: We employed the World Health Organisation’s (WHO) Cost Effectiveness Tool for Seasonal Influenza Vaccination (CETSIV), a decision tree model, to evaluate the 2018 seasonal influenza vaccination campaign from a public healthcare provider and societal perspective. CETSIV was populated with existing country-specific demographic, epidemiologic and coverage data to estimate incremental cost-effectiveness ratios (ICERs) by comparing costs and benefits of the influenza vaccination programme to no vaccination. RESULTS: The highest number of clinical events (influenza cases, outpatient visits, hospitalisation and deaths) were averted in PLWHA and persons with other UMCs. Using a cost-effectiveness threshold of US$ 3 400 per quality-adjusted life year (QALY), our findings suggest that the vaccination programme is cost-effective for all vulnerable populations except for children aged 6–59 months. ICERs ranged from ~US$ 1 750 /QALY in PLWHA to ~US$ 7 500/QALY in children. In probabilistic sensitivity analyses, the vaccination programme was cost-effective in pregnant women, PLWHA, persons with UMCs and persons aged ≥65 years in >80% of simulations. These findings were robust to changes in many model inputs but were most sensitive to uncertainty in estimates of influenza-associated illness burden. CONCLUSION: South Africa’s seasonal influenza vaccination strategy of opportunistically targeting vulnerable populations during routine visits is cost-effective. A budget impact analysis will be useful for supporting future expansions of the programme.